Calidad del entorno acústico basado en modelos para el ruido del tráfico vehicular en la zona urbana de la ciudad de Loja - Quevedo Pacheco, Erick Alexander (2021)
Through the information obtained, the urban area of the city of Loja poses high levels of noise (75 dB). So this study determined the quality of the acoustic environment, through the model of noise propagation in the urban area of the city, 580 noise measurements were obtained and urban noise maps were elaborated to reflect the degree of noise pollution, the urban area of Loja was classified according to the parishes with their functional characteristics and noise levels. Then the traffic noise assessment model was applied in which the exposed population and noise pollution in each parish are taken into account, in order to obtain the noise pollution index that allows determining the quality of the acoustic environment of the city. The propagation model shows that all parishes generate levels above 65 dB, mainly the parishes of Carigán and El Sagrario have the highest levels in the city with 71.1 dB. The evaluation of traffic noise obtained that the quality of the acoustic environment in the urban area is extremely polluting specifically in the parishes of El Valle, San Sebastián and Carigán. Key words: Noise pollution, noise propagation, acoustic environment